Killing Prescriptions Softly: Low Emission Zones and Child Health from Birth to School - Hannah Klauber; Felix Holub; Nicolas Koch; Nico Pestel; Nolan Ritter; Alexander Rohlf (Institute of Labor Economics (IZA), 2021)
We examine the persistence of the impact of early-life exposure to air pollution on children's health from birth to school enrollment using administrative public health insurance records covering one third of all children in Germany. For identification, we exploit air quality improvements caused by the implementation of Low Emission Zones, a policy imposing driving restrictions on high-emission vehicles. Our results indicate that children exposed to cleaner air around birth require less medication for at least five years. The initially latent health response materializes only gradually in lower medication usage, leaving important but subtle health benefits undetected in common measures of infant health.
Keywords: I18; Q51; Q53; Q58; 330; policy evaluation; cohort study; air pollution; health; children; Low Emission Zone